Peran penerimaan-penolakan orang tua terhadap presentasi diri daring pada remaja akhir pengguna Instagram - Prawira, Michelle Angela; Kesumaningsari, Ni Putu Adelia; Setiasih (Jurnal Psikologi Ulayat, 2025)
Instagram is one of the most widely used social media platforms, particularly among late adolescents, with 86.6% of global internet users actively engaging on the platform. Adolescents often hesitate to reveal their authentic selves online, instead curating idealized or false versions of themselves to seek acceptance, admiration, and positive impressions from their followers, which may carry adverse psychological consequences. This study investigates the influence of parental acceptance-rejection on adolescents’ online self-presentation on Instagram. Using a quantitative cross-sectional survey, data were collected from 207 adolescents (84.06% were female) aged 18 to 21 years. Participants completed the Parental Acceptance-Rejection Questionnaire (PARQ) and a modified Self-Presentation on Facebook Questionnaire (SPFBQ). Multiple regression analysis revealed that parental acceptance-rejection does not significantly predict adolescents’ presentasi diri daring Although parental acceptance-rejection plays important roles in adolescents’ socioemotional development, these factors do not appear to directly influence how they portray themselves on social media. The implications and limitations of these findings are further discussed.